Pengaruh Store Atmosphere Dan Word Of Mouth Terhadap Keputusan Pembelian Pada Labuana Resto & Cafe Makassar - Chandra , Meliana; Sampe, Ferdinandus; Tahendrika , Abner (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
This study aims to analyze the influence of store atmosphere and word of mouth on purchasing decisions at LaBuana Resto & Cafe Makassar. This study uses quantitative methods with the number of respondents being 98 visitors at LaBuana Resto & Café Makassar. Data collection is done by distributing questionnaires. The results of the calculation of the Store atmosphere variable (X1) on average of 4.06 which means most respondents agree on the statement items store atmosphere. While the results of the variable (X2) Word of mouth on average of 4.16, which means that most of the respondents agree with the statement items. The results showed that store atmosphere and word of mouth had a significant effect on purchasing decisions at Labuan Cafe & Restaurant Makassar, as evidenced by a significant value of 0.000 > 0.05. This proves that the store atmosphere and word of mouth have an effect on purchasing decisions at LaBuana Resto & Cafe Makassar.